German Bad Bank Plan: Government Should Take Over Toxic Assets at Zero Cost - Dorothea Schäfer; Klaus F. Zimmermann (Weekly Report, 2009)
With Germany's banking sector still suffering from the effects of the financial crisis, public discussion of plans to place toxic assets in one or more bad banks has gained steam in recent weeks. The following paper presents a bad bank plan from the German Institute for Economic Research. The key element of the plan is the valuation of troubled assets at their current market value - assets with no market would thus be valued at zero. The current shareholders will cover the losses arising from the depreciation reserve in the amount of the difference of the toxic assets' current book value and their market value. Under the plan, the government would bear responsibility for the management and future resale of toxic assets at its own cost and recapitalize the good bank by taking an equity stake in it. In extreme cases, this would mean a takeover of the bank by the government. The risk to taxpayers from this investment would be acceptable, however, once the banks are freed from toxic assets. A clear emphasis that the government stake is temporary would also be necessary. The government would cover the bad bank's losses, while profits would be distributed to the distressed bank's current shareholders. The plan is viable independent of whether the government decides to have one centralized bad bank or to establish a separate bad bank for each systemically relevant banking institute. Under the terms of the plan, bad banks and nationalization are not alternatives but rather two sides of the same coin. This plan effectively addresses three key challenges. It provides for the transparent removal of toxic assets and gives the banks a fresh start. At the same time, it offers the chance to keep the cost to taxpayers low. In addition, the risk of moral hazard is curtailed.
Keywords: G20; G24; G28; 330; Financial crisis; Bad bank; Recapitalization